Psychometric evaluation of the Urdu version of Inventory of Callous-Unemotional Traits: A multi-phase validation - Sania Mazher; Sobia Masood; Takashi Arai (PLoS ONE, 2026)
Callous-unemotional (CU) traits are central to the specifier with Limited Prosocial Emotions in the DSM-5 and ICD-11, reflecting severe emotional and behavioral disturbances. Despite the global use of the Inventory of Callous-Unemotional Traits (ICU), no validated version existed in Urdu. The aim of the present study was to translate, culturally adapt, and validate the Urdu version of the Inventory of Callous-Unemotional Traits (ICU-U) among Pakistani youth. The study consisted of three phases: translation and cultural adaptation of the instrument, assessment of test-retest reliability, and evaluation of structural validity through confirmatory factor analysis, alongside testing of convergent and discriminant validity. Test-retest reliability with bilingual youth (N = 60) was excellent, with the Urdu–Urdu condition demonstrating the highest stability. CFA conducted on a sample of 300 young adults (aged 18–25) supported a refined 12-item two-factor model (Callousness and Uncaring) over the original three-factor and bifactor models, aligning with previous international findings. Internal consistency for both subscales was satisfactory, and the ICU-U demonstrated strong convergent and discriminant validity through expected associations with criminal sentiments and self-control measures. The findings establish the ICU-U as a culturally relevant and psychometrically sound instrument for identifying CU traits in Urdu-speaking populations. Its use holds promise in clinical, educational, and forensic settings for early detection and intervention planning.